Politik Seksual dalam Tafsir al-Qur'an tentang Sejarah Homoseksualitas - Muhammad Dluha Luthfillah; Muhammad Imdad Ilhami Khalil (UIN Sunan Kalijaga Yogyakarta, 2018)
Homophobic bias has been existing in tafsir literature, ranging from its very early works to the most recent ones. Among the aspects in which such a bias appears is that relating to the history of homosexuality. Al-A’rāf ([7]: 80) and al-‘Ankabūt ([29]: 28) are the only verses that talk about the aspect. Rather than following the mainstream tafsir denying the historicity of homosexuality, this article elaborates al-Rāzī’s alternative interpretation on the two verses and comes up with an argument that homosexuality might historically exist even before the lifetime of Lot and his people. Emphasizing on linguistic and literary analysis on the words sabaqa, bi, and fahisya, it finds strong foundations on which the argument is relying. Further, the article finds that it is the sexual politics that brings about the homophobic bias into Qur’an tafsir. The very kind of politics expels homosexuality from the so- called ‘normal’ life.